Exploring careers through a qualitative lens: an investigation and invitation. Issue 1 (27th December 2021) - Richardson, Julia; O'Neil, Deborah Anne; Thorn, Kaye
Abstract : Purpose: In this paper, the authors investigate and celebrate the contributions that qualitative research has made to Career Development International (CDI) and careers scholarship over the past 25 years. The authors highlight the positive impact of understanding the "lived/emic experiences" of individual career actors using qualitative research designs and identify areas for future research. Design/methodology/approach: The authors employ multiple approaches in their investigation. The authors' enquiry is part conceptual, part critical analysis and part bibliometric visualisation of qualitative papers published in CDI. Findings: The authors identify the underlying ontological and epistemological assumptions of qualitative research, and the key tenets and contributions of qualitative research published in CDI. Their bibliometric analysis shows the interrelatedness and frequency of topics addressed by qualitative research and published in CDI, revealing areas for further research. While identifying some of the key criteria for rigor in qualitative research, the authors also engage with emerging calls to avoid rigid templates in how qualitative research is designed and implemented. In this regard, authors echo calls for "methodological bricolage" as an approach to qualitative research in the study of careers. Originality/value: This is the first bibliographic and visual analysis of qualitative research published in a single journal. The authors offer this investigation as a way of looking back and as an invitation looking forward, encouraging further qualitative research in anticipation of future theoretical developments in career scholarship.